Lithium iron phosphate modified material as well as preparation method and application thereof
By constructing structural defects in lithium iron phosphate materials and introducing transition metal doped layers, the interfacial side reaction problems caused by the release of oxygen by lithium supplement agents are solved, and high energy density, high power and excellent battery performance are achieved.
Patent Information
- Application Number
- CN202411593179.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-02-18
AI Technical Summary
During the charging and discharging process, the interfacial side reactions caused by the release of oxygen by lithium iron phosphate batteries affect the performance of the battery, especially in terms of high-temperature storage and safety.
By constructing structural defective lithium iron phosphate modified materials, a transition metal doped layer and a carbon layer are introduced to absorb the oxygen released by the lithium supplement agent during the deliquification process, thereby reducing the interfacial side reaction.
The lithium iron phosphate positive electrode material with high energy density and high power characteristics is achieved, while avoiding the adverse effects of oxygen release from lithium supplement agents, improving the safety of the battery and high-temperature storage performance.
Smart Images

Figure CN119480975A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of battery materials, and in particular relates to a lithium iron phosphate modified material and a preparation method and application thereof. Background Art
[0002] Lithium iron phosphate (LiFePO4, LFP for short) is a lithium-ion battery cathode material. Due to its stable olivine structure, long cycle life, safety and non-toxicity, and low cost, it is widely used in power, energy storage, power tools, two-wheeled vehicles and other fields. Compared with other cathode materials (lithium cobalt oxide (LiCoO2), lithium nickel cobalt manganese oxide (Li(Ni x Co y Mn z Compared with lithium iron phosphate, lithium iron phosphate has low gram capacity (actual specific capacity is about 140mAh / g), low voltage platform (about 3.2V), Li + To overcome the above shortcomings, lithium supplementation is an important way to improve energy density and power in practical applications. By adding a small amount of positive electrode lithium supplement, such as lithium iron-rich lithium (Li5FeO4, referred to as LFO) and lithium nickel oxide (Li2NiO2, referred to as LNO), the conversion efficiency of the positive and negative electrodes can be balanced, thereby improving the overall energy efficiency of the battery, maximizing the energy, and improving Li + The transmission efficiency is improved and the power characteristics of LFP are improved.
[0003] Introducing lithium supplements into lithium iron phosphate cathode materials is an effective method for synthesizing high-energy lithium iron phosphate materials, but the accompanying gas production problem will bring about a series of irreversible interface side reactions during the charge and discharge process, thereby affecting the performance of lithium iron phosphate batteries, especially service life, high-temperature storage, safety, etc. Taking LFO as an example, when the battery is working, as the voltage increases, LFO releases Li + During the process, Fe ions will undergo redox reactions, accompanied by the generation of oxygen. Some of the oxygen will diffuse to the negative electrode to participate in the reconstruction of the solid electrolyte interface film (SEI), some of the oxygen will be discharged during the battery cell formation stage, and some of the oxygen will dissolve in the electrolyte, causing solvent decomposition, resulting in severe gas production. When the amount of lithium supplement added is small, SEI will completely consume it to release oxygen, and will not damage the battery cell; but when the amount added is large, it will worsen the interface side reaction of the positive electrode material, resulting in severe gas production in the battery cell, especially the rapid decay of high-temperature storage performance.
[0004] To solve this problem, the existing technology has coated Li2NiO2 on the surface of LFO to inhibit the oxidation of LFO and improve the performance of the battery; some have introduced catalysts into conventional lithium supplements to reduce the decomposition voltage of lithium-rich materials, reduce the release of oxygen, and improve the cycle and safety performance of the battery; and synthesized a lithium supplement by adding a conductive agent to improve its electron mobility and reduce the catalytic delithiation potential, thereby obtaining a stable low decomposition potential lithium supplement. That is, the existing technology mainly reduces its interfacial activity or decomposition voltage by coating or compounding (catalyst, conductive agent) on the lithium supplement, thereby reducing the release of oxygen during the charging process of the lithium supplement, inhibiting oxygen-induced electrolyte solvent ring opening and gas production, thereby reducing a series of side reactions caused by it, especially electrical properties such as high-temperature storage. However, the above measures still have some limitations. On the one hand, some inactive substances will be introduced, thereby reducing the lithium supplement efficiency of the lithium supplement; on the other hand, according to the law of conservation of charge, Li in the lithium supplement LFO + The release of lithium will inevitably lead to the generation of oxygen, and the above method is difficult to fundamentally solve the gas production problem of lithium supplements. Summary of the invention
[0005] In order to overcome at least one of the problems existing in the above-mentioned prior art, one of the objects of the present invention is to provide a lithium iron phosphate modified material. By constructing structural defects, the lithium iron phosphate modified material can effectively absorb the oxygen released by the lithium supplement during the delithiation process. Therefore, the composite electrode material after mixing with the lithium supplement has the characteristics of high energy density, high power, etc., and can avoid the adverse effects of oxygen release from the lithium supplement.
[0006] A second object of the present invention is to provide a method for preparing a lithium iron phosphate modified material.
[0007] A third object of the present invention is to provide a lithium iron phosphate positive electrode material.
[0008] A fourth object of the present invention is to provide a battery.
[0009] In order to achieve the above object, the technical solution adopted by the present invention is:
[0010] The first aspect of the present invention provides a lithium iron phosphate modified material, comprising: lithium iron phosphate particles, a coating layer coated on at least a portion of the surface of the lithium iron phosphate particles, and a carbon layer coated on at least a portion of the surface of the coating layer; the coating layer includes a transition metal doping layer, and the transition metal doping layer contains structural defects.
[0011] The lithium iron phosphate modified material according to the first aspect of the present invention has at least the following beneficial effects:
[0012] The present invention is based on the improvement of the lithium iron phosphate material itself, and introduces a transition metal doping layer, wherein the doped transition metal element will generate holes or electrons in the material, thereby forming structural defects such as oxygen defects, thereby facilitating the absorption of oxygen by the material, and reducing the adverse effects of the release of oxygen by the lithium supplement. In addition, the doped transition metal element is also beneficial to reducing the valence of metal cations in the lithium supplement, for example, it can reduce the valence of Fe ions in lithium-rich ferroic acid (LFO), thereby reducing the release of oxygen. By using the lithium iron phosphate modified material provided by the present invention in combination with the lithium supplement, there is no need to coat and modify the lithium supplement, nor is there any need to introduce inactive substances such as oxygen absorbers, thereby effectively solving the gas production problem of the lithium supplement without affecting the lithium supplement efficiency and electrochemical performance of the material, and thus obtaining a high-energy, high-power lithium iron phosphate positive electrode material and a lithium ion battery.
[0013] In some specific embodiments of the present invention, the structural defects in the transition metal doped layer include oxygen defects.
[0014] In some specific embodiments of the present invention, the coating layer further comprises a transition metal oxide layer, and the transition metal oxide layer coats at least a portion of the surface of the transition metal doping layer.
[0015] In some specific embodiments of the present invention, the lithium iron phosphate particles contain structural defects.
[0016] In some specific embodiments of the present invention, the structural defects in the lithium iron phosphate particles include at least one of Li-Fe antisite defects, dislocations or oxygen defects.
[0017] In some specific embodiments of the present invention, the transition metal element doped in the transition metal doping layer includes at least one of Ti, Ni, Y, Fe, Ce, W or Co.
[0018] In some specific embodiments of the present invention, the content of transition metal elements in the coating layer is 0.1-1 wt%.
[0019] The present invention only needs to introduce less transition metal elements to improve the energy density and power of the lithium iron phosphate modified material, has good modification effect, and has obvious cost advantages.
[0020] The second aspect of the present invention provides a method for preparing a lithium iron phosphate modified material, comprising the following steps: mixing a transition metal oxide with a carbon source and pretreating the mixture, adding an iron source, a lithium source, and a phosphorus source to mix the mixture, and then sintering the mixture to obtain the lithium iron phosphate modified material as described in the first aspect of the present invention.
[0021] The method for preparing the lithium iron phosphate modified material according to the second aspect of the present invention has at least the following beneficial effects:
[0022] The iron source, lithium source, and phosphorus source will form lithium iron phosphate during the sintering process, and the added carbon source can act as a reducing agent to promote the reduction of part of the trivalent iron source, thereby facilitating the formation of lithium iron phosphate particles; in addition, the carbon source can also reduce transition metal oxides, changing the oxidation state of the transition metal elements from M to n+ Transformed to M (n-1)+ (M refers to the transition metal element, and n refers to the valence state of the transition metal element in the transition metal oxide), forming a transition metal cation with a lower valence state, which will occupy the metal site of the outer layer of lithium iron phosphate, thereby forming a transition metal doping layer; in this process, the carbon source is carbonized to form a conductive carbon layer, which is coated on the surface of the material to improve the electrochemical performance of the material. Mixing the transition metal oxide with the carbon source for pretreatment is conducive to the built-in oxygen defects in the material, and the transition metal oxide surface is disordered, and its electronic structure is changed to produce oxygen defects. In addition, the transition metal oxide and the carbon source are fully mixed, which can improve the coating uniformity of the transition metal oxide on the surface of the lithium iron phosphate particles, and the carbon source itself, as a reducing agent, is helpful to the construction of oxygen defects in the transition metal doping layer. Through the preparation method of the present invention, a lithium iron phosphate modified material with a specific coating structure and built-in structural defects can be simply and efficiently prepared, so that the gas production problem of the lithium supplement agent is effectively solved without coating and modifying the lithium supplement agent or introducing inactive substances such as oxygen absorbers, thereby obtaining a high-energy, high-power lithium iron phosphate positive electrode material.
[0023] In some specific embodiments of the present invention, the heating rate of the sintering is 8000-12000° C. / min.
[0024] In the present invention, by optimizing the sintering curve, a faster heating rate is adopted to achieve rapid heating, and the sintering is controlled to be short-term, so that Li + or Fe 2+ During the heating process, there is not enough time to diffuse to the equilibrium position, resulting in Li-Fe anti-location, dislocation and other defects, and tensile strain, which increases the Li + Diffusion efficiency. The existence of Li-Fe antisite defects is Li + Two-dimensional diffusion provides new channels, and the tensile strain field reduces the Li + Energy barriers of two-dimensional diffusion paths; when Li-Fe antisite defects and tensile strain coexist, they can effectively reduce the Li + Diffusion anisotropy, realizing Li + Two-dimensional diffusion increases the rate performance of lithium iron phosphate materials, and the introduction of defects is conducive to the absorption of oxygen, reducing the adverse effects of oxygen released by lithium supplements.
[0025] In some specific embodiments of the present invention, the heating time of sintering is 1 to 5 seconds.
[0026] In some specific embodiments of the present invention, the sintering temperature reduction rate is 8000-12000° C. / min.
[0027] In some specific embodiments of the present invention, the sintering temperature reduction time is 1 to 5 seconds.
[0028] In some specific embodiments of the present invention, the sintering temperature is 700-900°C.
[0029] At the sintering temperature of the present invention, it is beneficial to dope the transition metal elements on the surface of the lithium iron phosphate particles, thereby forming a transition metal doping layer, and some of the undoped transition metal oxides will be coated on the surface of the transition metal doping layer in the form of physical coating, as a transition metal oxide layer, and together with the transition metal doping layer serve as a coating layer.
[0030] In some specific embodiments of the present invention, the sintering holding time is 10 to 100 seconds.
[0031] In some specific embodiments of the present invention, the sintering is performed in a protective gas atmosphere.
[0032] In some specific embodiments of the present invention, the pretreatment method includes ball milling, ultrasonic treatment or a combination thereof.
[0033] Mixing the transition metal oxide with the carbon source and subjecting them to ball milling and / or ultrasonic treatment can disorder the surface of the transition metal oxide through the shearing action of ball milling or the ultrasonic wave of ultrasonic treatment, change its electronic structure and thus produce oxygen defects. In addition, fully mixing the transition metal oxide and the carbon source is beneficial to improving the coating uniformity of the transition metal oxide on the lithium iron phosphate material, and the carbon source itself, as a reducing agent, can promote the construction of oxygen defects in the transition metal oxide.
[0034] In some specific embodiments of the present invention, the ball milling time is 12 to 60 hours.
[0035] In some specific embodiments of the present invention, the ultrasonic treatment time is 0.1 to 5 hours.
[0036] In some specific embodiments of the present invention, the ultrasonic frequency of the ultrasonic treatment is 10 to 50 kHz.
[0037] In some specific embodiments of the present invention, before the transition metal oxide is mixed with the carbon source for pretreatment, the process further includes ball milling the transition metal oxide.
[0038] Through ball milling treatment, shear force and pressure are applied to transition metal oxides, which will introduce a large amount of lattice distortion, causing oxygen atoms to leave their original lattice positions and introduce oxygen defects.
[0039] In some specific embodiments of the present invention, the ball milling speed for ball milling the transition metal oxide is 500-1500 r / min.
[0040] In some specific embodiments of the present invention, the ball milling time for the transition metal oxide is 0.5 to 5 hours.
[0041] In some specific embodiments of the present invention, the transition metal oxide includes at least one of TiO2, NiO, Y2O3, Fe2O3, CeO2, WO3 or Co3O4.
[0042] In some specific embodiments of the present invention, the mass ratio of the iron source to the transition metal oxide is 1:(0.001-0.1).
[0043] The content of transition metal oxides required to be added in the present invention is small, and the metal elements are abundant in resources, and the cost is low. Compared with other improvement methods, the present invention has obvious advantages in terms of cost.
[0044] The third aspect of the present invention provides a lithium iron phosphate positive electrode material, including a positive electrode lithium supplement, and the lithium iron phosphate modified material described in the first aspect of the present invention or the lithium iron phosphate modified material prepared by the preparation method described in the second aspect of the present invention.
[0045] The lithium iron phosphate positive electrode material according to the third aspect of the present invention has at least the following beneficial effects:
[0046] The lithium iron phosphate modified material provided by the present invention has a good absorption effect on oxygen by introducing structural defects. Therefore, when combined with a positive electrode lithium replenisher, it can effectively absorb the oxygen generated by the positive electrode lithium replenisher, thereby solving the gas production problem caused by the introduction of the positive electrode lithium replenisher, thereby obtaining a high-energy, high-power lithium iron phosphate positive electrode material.
[0047] In some specific embodiments of the present invention, the positive electrode lithium supplement includes lithium-rich lithium ferrite, lithium nickelate or a combination thereof.
[0048] In some specific embodiments of the present invention, the content of the positive electrode lithium replenisher in the lithium iron phosphate positive electrode material is 0.3-2 wt %.
[0049] The fourth aspect of the present invention provides a battery, comprising the lithium iron phosphate positive electrode material described in the third aspect of the present invention.
[0050] The battery according to the fourth aspect of the present invention has at least the following beneficial effects:
[0051] The lithium iron phosphate positive electrode material provided by the present invention has low gas production and has the characteristics of high energy and high power. A battery with excellent electrochemical performance can be obtained by using it as a positive electrode material. BRIEF DESCRIPTION OF THE DRAWINGS
[0052] Figure 1 This is a schematic diagram of the structure of the lithium iron phosphate modified material of Example 1.
[0053] Figure 2 This is a flow chart for preparing the lithium iron phosphate modified material of Example 1.
[0054] Figure 3 This is a SEM image of a portion of the lithium iron phosphate modified material of Example 1.
[0055] Figure 4 This is a SEM image of another part of the lithium iron phosphate modified material of Example 1.
[0056] Figure 5 This is a schematic diagram of the structure of the lithium iron phosphate modified material of Comparative Example 1. DETAILED DESCRIPTION
[0057] The content of the present invention is further described in detail below through specific examples. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the principles set forth in the present invention all belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are also only examples within a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not limited to the specific data exemplified below. The raw materials, reagents or devices used in the following examples and comparative examples, unless otherwise specified, can all be obtained from conventional commercial sources, or can be obtained by existing known methods.
[0058] A first aspect of an embodiment of the present invention provides a lithium iron phosphate modified material, comprising: lithium iron phosphate particles, a coating layer coated on at least a portion of the surface of the lithium iron phosphate particles, and a carbon layer coated on at least a portion of the surface of the coating layer; the coating layer includes a transition metal doping layer, and the transition metal doping layer contains structural defects.
[0059] In the embodiment of the present invention, based on the improvement of the lithium iron phosphate material itself, a transition metal doping layer is introduced, wherein the doped transition metal element will generate holes or electrons in the material, thereby forming structural defects such as oxygen defects, thereby facilitating the absorption of oxygen by the material and reducing the adverse effects of the release of oxygen by the lithium supplement. In addition, the doped transition metal element is also beneficial to reducing the valence of metal cations in the lithium supplement, for example, it can reduce the valence of Fe ions in lithium-rich ferroic acid (LFO), thereby reducing the release of oxygen. By using the lithium iron phosphate modified material provided by the present invention in combination with the lithium supplement, there is no need to coat and modify the lithium supplement, nor is there any need to introduce inactive substances such as oxygen absorbers, thereby effectively solving the gas production problem of the lithium supplement without affecting the lithium supplement efficiency and electrochemical performance of the material, and thus obtaining a high-energy, high-power lithium iron phosphate positive electrode material and a lithium ion battery.
[0060] In the present invention, the transition metal doped layer refers to a layer structure doped with transition metal elements; the structural defect refers to the distortion of the periodic potential field in the crystal lattice structure.
[0061] In some embodiments of the present invention, the structural defects in the transition metal doped layer include oxygen defects.
[0062] In the present invention, oxygen defects refer to non-ideal arrangements or absences of oxygen atoms, including oxygen vacancies (defects formed when oxygen atoms in a crystal are separated from the crystal lattice), oxygen atoms are replaced by other types of atoms, or oxygen atoms are exchanged with atoms at other positions in the crystal lattice.
[0063] In the embodiment of the present invention, the oxygen defects in the transition metal doping layer are mainly caused by the introduction of transition metal elements. The transition metal elements are introduced in the form of transition metal oxides. In the process of forming the coating layer, the transition metal oxides are reduced to form metal cations with lower valence, and the oxidation state changes from M to n+ Transformed to M (n-1)+ (M refers to the transition metal element, and n refers to the valence state of the transition metal element in the transition metal oxide). In this process, oxygen is removed, resulting in the redistribution of excess electrons on the vacant energy levels of the cation to form oxygen defects.
[0064] In some embodiments of the present invention, the coating layer further includes a transition metal oxide layer, and the transition metal oxide layer coats at least a portion of the surface of the transition metal doping layer.
[0065] In an embodiment of the present invention, the transition metal elements in the transition metal doping layer are introduced in the form of transition metal oxides. Most of the transition metal oxides will form metal cations during the high-temperature sintering process, thereby occupying the metal sites of the lithium iron phosphate particles, thereby forming a transition metal doping layer. Some transition metal oxides may not form doping, but are physically coated on the surface of the transition metal doping layer to form a transition metal oxide layer, which can protect the inner layer structure.
[0066] In some embodiments of the present invention, lithium iron phosphate particles contain structural defects; in some specific embodiments of the present invention, the structural defects in the lithium iron phosphate particles include at least one of Li-Fe antisite defects, dislocations or oxygen defects; in some examples of the present invention, the structural defects in the lithium iron phosphate particles include Li-Fe antisite defects, dislocations or a combination thereof.
[0067] Structural defects are also introduced into lithium iron phosphate particles, among which Li-Fe antisite defects and dislocations are conducive to further diffusion of Li + diffusion channel, reducing Li + The energy barrier of the two-dimensional diffusion path increases the Li + Diffusion efficiency and material rate performance, as well as oxygen defects, are conducive to enhancing the oxygen absorption capacity, further reducing the adverse effects of oxygen released by lithium supplements. Among them, Li-Fe antisite defects refer to the phenomenon that the positions of Li atoms and Fe atoms in the crystal structure of lithium iron phosphate are interchanged; dislocations refer to linear defects in the crystal structure that deviate from the ideal arrangement.
[0068] In some embodiments of the present invention, structural defects are introduced into lithium iron phosphate particles by high-temperature rapid sintering. Through high-temperature rapid sintering, Li atoms and Fe atoms do not have enough time to diffuse to equilibrium positions during the heating process, thereby generating defects such as Li-Fe antilocations and dislocations, and generating tensile strain.
[0069] Li-Fe antisite defects are mainly caused by Li + with Fe 2+ Site exchange, generating new Li + Two-dimensional transmission channel, high-temperature rapid sintering combined with rapid annealing, so that the material retains the lattice expansion at high temperature, producing a vertical Li + The tensile strain field on the ac plane of the main transport direction reduces the Li + Two-dimensional transport energy barrier, improving Li + Diffusion efficiency and rate performance of materials.
[0070] In some embodiments of the present invention, the transition metal element doped in the transition metal doping layer includes at least one of Ti, Ni, Y, Fe, Ce, W or Co; in some embodiments of the present invention, the transition metal element doped in the transition metal doping layer includes at least two of Ti, Ni, Y, Fe, Ce, W or Co.
[0071] In some embodiments of the present invention, the content of transition metal elements in the coating layer is 0.1-1wt%; in some specific embodiments of the present invention, the content of transition metal elements in the coating layer is 0.15-0.9wt%; in some examples of the present invention, the content of transition metal elements in the coating layer is 0.2-0.8wt%; non-limiting specific examples are 0.2wt%, 0.25wt%, 0.3wt%, 0.35wt%, 0.4wt%, 0.45wt%, 0.5wt%, 0.55wt%, 0.6wt%, 0.65wt%, 0.7wt%, 0.75wt% or 0.8wt%.
[0072] The present invention only needs to add less transition metal elements to improve the energy density and power of the lithium iron phosphate modified material, has good modification effect, and has obvious cost advantages.
[0073] The second aspect of an embodiment of the present invention provides a method for preparing a lithium iron phosphate modified material, comprising the following steps: mixing a transition metal oxide with a carbon source and pretreating the mixture, adding an iron source, a lithium source, and a phosphorus source to mix the mixture, and then sintering the mixture to obtain the lithium iron phosphate modified material according to the first aspect of the embodiment of the present invention.
[0074] The iron source, lithium source, and phosphorus source will form lithium iron phosphate during the sintering process, and the added carbon source can act as a reducing agent to promote the reduction of part of the trivalent iron source, thereby facilitating the formation of lithium iron phosphate particles; in addition, the carbon source can also reduce transition metal oxides, changing the oxidation state of the transition metal elements from M to n+ Transformed to M (n-1)+(M refers to the transition metal element, and n refers to the valence state of the transition metal element in the transition metal oxide), forming a transition metal cation with a lower valence state, which will occupy the metal site of the outer layer of lithium iron phosphate, thereby forming a transition metal doping layer; in this process, the carbon source is carbonized to form a conductive carbon layer, which is coated on the surface of the material to improve the electrochemical performance of the material. Mixing the transition metal oxide with the carbon source for pretreatment is conducive to the built-in oxygen defects in the material, and the transition metal oxide surface is disordered, and its electronic structure is changed to produce oxygen defects. In addition, the transition metal oxide and the carbon source are fully mixed, which can improve the coating uniformity of the transition metal oxide on the surface of the lithium iron phosphate particles, and the carbon source itself, as a reducing agent, is helpful to the construction of oxygen defects in the transition metal doping layer. Through the preparation method of the present invention, a lithium iron phosphate modified material with a specific coating structure and built-in structural defects can be simply and efficiently prepared, so that the gas production problem of the lithium supplement agent is effectively solved without coating and modifying the lithium supplement agent or introducing inactive substances such as oxygen absorbers, and a high-energy, high-power lithium iron phosphate positive electrode material is obtained.
[0075] In some embodiments of the present invention, sintering is performed by high temperature superconducting heating.
[0076] In some embodiments of the present invention, the sintering heating rate is 8000-12000°C / min; in some specific embodiments of the present invention, the sintering heating rate is 8500-11500°C / min; in some examples of the present invention, the sintering heating rate is 9000-11000°C / min; non-limiting specific examples are 9000°C / min, 9200°C / min, 9500°C / min, 9800°C / min, 10000°C / min, 10200°C / min, 10500°C / min, 10800°C / min or 11000°C / min.
[0077] In the embodiment of the present invention, by optimizing the sintering curve, a faster heating rate is adopted to achieve rapid heating, and the sintering is controlled to be short-term, so that Li + or Fe 2+ During the heating process, there is not enough time to diffuse to the equilibrium position, resulting in Li-Fe anti-location, dislocation and other defects, and tensile strain, which increases the Li + Diffusion efficiency. The existence of Li-Fe antisite defects is Li + Two-dimensional diffusion provides new channels, and the tensile strain field reduces the Li + Energy barriers of two-dimensional diffusion paths; when Li-Fe antisite defects and tensile strain coexist, they can effectively reduce the Li + Diffusion anisotropy, realizing Li +Two-dimensional diffusion increases the rate performance of lithium iron phosphate materials, and the introduction of defects is conducive to the absorption of oxygen, reducing the adverse effects of oxygen released by lithium supplements.
[0078] In some embodiments of the present invention, the sintering heating time is 1 to 5 s; in some specific embodiments of the present invention, the sintering heating time is 1.2 to 4 s; in some examples of the present invention, the sintering heating time is 1.5 to 3 s; non-limiting specific examples are 1.5 s, 1.8 s, 2 s, 2.2 s, 2.5 s, 2.8 s or 3 s.
[0079] In some embodiments of the present invention, the sintering cooling rate is 8000-12000°C / min; in some specific embodiments of the present invention, the sintering cooling rate is 8500-11500°C / min; in some examples of the present invention, the sintering cooling rate is 9000-11000°C / min; non-limiting specific examples are 9000°C / min, 9200°C / min, 9500°C / min, 9800°C / min, 10000°C / min, 10200°C / min, 10500°C / min, 10800°C / min or 11000°C / min.
[0080] In some embodiments of the present invention, the sintering cooling time is 1 to 5 s; in some specific embodiments of the present invention, the sintering cooling time is 1.2 to 4 s; in some examples of the present invention, the sintering cooling time is 1.5 to 3 s; non-limiting specific examples are 1.5 s, 1.8 s, 2 s, 2.2 s, 2.5 s, 2.8 s or 3 s.
[0081] In some embodiments of the present invention, the sintering temperature is 700-900°C; in some specific embodiments of the present invention, the sintering temperature is 780-880°C; in some examples of the present invention, the sintering temperature is 750-850°C; non-limiting specific examples are 750°C, 760°C, 780°C, 800°C, 820°C, 840°C or 850°C.
[0082] At the sintering temperature of the embodiment of the present invention, it is conducive to the doping of transition metal elements on the surface of the lithium iron phosphate particles, thereby forming a transition metal doping layer, and some undoped transition metal oxides will be coated on the surface of the transition metal doping layer in the form of physical coating, as a transition metal oxide layer, and together with the transition metal doping layer serve as a coating layer.
[0083] In some embodiments of the present invention, the holding time for sintering is 10 to 100 s; in some specific embodiments of the present invention, the holding time for sintering is 15 to 80 s; in some examples of the present invention, the holding time for sintering is 23 to 60 s; non-limiting specific examples are 23 s, 25 s, 30 s, 35 s, 40 s, 45 s, 50 s, 55 s or 60 s.
[0084] In some embodiments of the present invention, sintering is performed in a protective gas atmosphere; in some specific embodiments of the present invention, the protective gas includes at least one of nitrogen, argon or helium; in some examples of the present invention, the protective gas includes nitrogen, argon or a combination thereof.
[0085] In some embodiments of the present invention, the purity of the protective gas atmosphere for sintering is ≥99%; in some specific embodiments of the present invention, the purity of the protective gas atmosphere for sintering is ≥99.9%; non-limiting examples include 99.9%, 99.95%, 99.99%, etc.
[0086] In some embodiments of the present invention, the oxygen content in the sintering atmosphere is ≤50 ppm; non-limiting examples include 50 ppm, 40 ppm, 30 ppm, 20 ppm, 10 ppm, etc.
[0087] In some embodiments of the present invention, the pretreatment method after mixing the transition metal oxide and the carbon source includes ball milling, ultrasonic treatment or a combination thereof; in some specific embodiments of the present invention, the pretreatment method includes ball milling and ultrasonic treatment.
[0088] Mixing the transition metal oxide with the carbon source and subjecting them to ball milling and / or ultrasonic treatment can disorder the surface of the transition metal oxide through the shearing action of ball milling or the ultrasonic wave of ultrasonic treatment, change its electronic structure and thus produce oxygen defects. In addition, fully mixing the transition metal oxide and the carbon source is beneficial to improving the coating uniformity of the transition metal oxide on the lithium iron phosphate material, and the carbon source itself, as a reducing agent, can promote the construction of oxygen defects in the transition metal oxide.
[0089] In some embodiments of the present invention, during the pretreatment, the ball milling time is 12 to 60 hours; in some specific embodiments of the present invention, during the pretreatment, the ball milling time is 18 to 52 hours; in some examples of the present invention, during the pretreatment, the ball milling time is 24 to 48 hours; non-limiting specific examples are 24 hours, 26 hours, 30 hours, 35 hours, 40 hours, 45 hours or 48 hours.
[0090] In some embodiments of the present invention, in the pretreatment, the ball milling is specifically wet ball milling.
[0091] In some embodiments of the present invention, during the pretreatment, the ultrasonic time of the ultrasonic treatment is 0.1 to 5 h; in some specific embodiments of the present invention, during the pretreatment, the ultrasonic time of the ultrasonic treatment is 0.3 to 3 h; in some examples of the present invention, during the pretreatment, the ultrasonic time of the ultrasonic treatment is 0.5 to 2 h; non-limiting specific examples are 0.5 h, 0.8 h, 1 h, 1.2 h, 1.5 h, 1.8 h or 2 h.
[0092] In some embodiments of the present invention, during the pretreatment, the ultrasonic frequency of the ultrasonic treatment is 10 to 50 kHz; in some specific embodiments of the present invention, during the pretreatment, the ultrasonic frequency of the ultrasonic treatment is 15 to 45 kHz; in some examples of the present invention, during the pretreatment, the ultrasonic frequency of the ultrasonic treatment is 20 to 40 kHz; non-limiting specific examples are 20 kHz, 22 kHz, 25 kHz, 28 kHz, 30 kHz, 32 kHz, 35 kHz, 38 kHz or 40 kHz.
[0093] In some embodiments of the present invention, before the transition metal oxide is mixed with the carbon source for pretreatment, the process further includes the step of ball milling the transition metal oxide.
[0094] Through ball milling treatment, shear force and pressure are applied to transition metal oxides, which will introduce a large amount of lattice distortion, causing oxygen atoms to leave their original lattice positions and introduce oxygen defects.
[0095] In some embodiments of the present invention, the ball milling speed for ball milling the transition metal oxide is 500-1500 r / min; in some specific embodiments of the present invention, the ball milling speed for ball milling the transition metal oxide is 700-1300 r / min; in some examples of the present invention, the ball milling speed for ball milling the transition metal oxide is 800-1200 r / min; non-limiting specific examples are 800 r / min, 850 r / min, 900 r / min, 950 r / min, 1000 r / min, 1050 r / min, 1100 r / min, 1150 r / min or 1200 r / min.
[0096] In some embodiments of the present invention, the ball milling time for the transition metal oxide is 0.5 to 5 hours; in some specific embodiments of the present invention, the ball milling time for the transition metal oxide is 0.8 to 4 hours; in some examples of the present invention, the ball milling time for the transition metal oxide is 1 to 3 hours; non-limiting specific examples are 1 hour, 1.2 hours, 1.5 hours, 1.8 hours, 2 hours, 2.2 hours, 2.5 hours, 2.8 hours or 3 hours.
[0097] In some embodiments of the present invention, the transition metal oxide includes at least one of TiO2, NiO, Y2O3, Fe2O3, CeO2, WO3 or Co3O4; in some specific embodiments of the present invention, the transition metal oxide includes at least one of TiO2, NiO, Y2O3 or Co3O4; in some examples of the present invention, the transition metal oxide includes TiO2, Co3O4 or a combination thereof.
[0098] In some embodiments of the present invention, the mass ratio of the iron source to the transition metal oxide is 1:(0.001-0.1); in some embodiments of the present invention, the mass ratio of the iron source to the transition metal oxide is 1:(0.002-0.07); in some embodiments of the present invention, the mass ratio of the iron source to the transition metal oxide is 1:(0.003-0.05); non-limiting specific examples are 1:0.003, 1:0.005, 1:0.01, 1:0.015, 1:0.02, 1:0.03, 1:0.04 or 1:0.05.
[0099] The content of transition metal oxides required to be added in the embodiments of the present invention is small, and the metal elements are abundant in resources, and the cost is low. Compared with other improvement methods, the present invention has obvious advantages in terms of cost.
[0100] In some embodiments of the present invention, the carbon source includes at least one of sugars, alcohols, esters, acids or resins; in some specific embodiments of the present invention, the carbon source includes sugars, alcohols or a combination thereof; in some examples of the present invention, the carbon source is selected from sugars.
[0101] In some embodiments of the present invention, the carbon source includes at least one of glucose, sucrose, starch, polyvinyl alcohol, xylitol, ethyl acetate, amino acids, malic acid, citric acid or phenolic resin; in some specific embodiments of the present invention, the carbon source includes at least one of glucose, sucrose, starch, polyvinyl alcohol or xylitol; in some examples of the present invention, the carbon source is selected from glucose.
[0102] In some embodiments of the present invention, the mass ratio of the iron source to the carbon source is 1:(0.5-3); in some embodiments of the present invention, the mass ratio of the iron source to the carbon source is 1:(0.8-2); in some embodiments of the present invention, the mass ratio of the iron source to the carbon source is 1:(1-1.5); non-limiting specific examples are 1:1, 1:1.1, 1:1.2, 1:1.3, 1:1.4 or 1:1.5.
[0103] In some embodiments of the present invention, the iron source includes a ferrous iron source, a ferric iron source, or a combination thereof; in some specific embodiments of the present invention, the iron source is selected from a ferrous iron source.
[0104] In some embodiments of the present invention, the iron source includes at least one of ferrous oxalate, ferrous sulfate, ferrous chloride, ferrous nitrate, ferrous carbonate, ferrous sulfide, ferrous hydroxide, ferrous tetroxide, ferric phosphate, ferric hydroxide, ferric oxide or ferric oxyhydroxide; in some specific embodiments of the present invention, the iron source includes at least one of ferrous oxalate, ferrous sulfate, ferrous chloride, ferrous nitrate, ferrous carbonate, ferrous sulfide or ferrous hydroxide; in some examples of the present invention, the iron source is selected from ferrous oxalate.
[0105] In some embodiments of the present invention, the lithium source includes at least one of lithium carbonate, lithium hydroxide, lithium phosphate, lithium dihydrogen phosphate or lithium acetate; in some specific embodiments of the present invention, the lithium source includes at least one of lithium carbonate, lithium hydroxide or lithium phosphate; in some examples of the present invention, the lithium source is selected from lithium carbonate.
[0106] In some embodiments of the present invention, the mass ratio of the iron source to the lithium source is 1:(0.5-2); in some embodiments of the present invention, the mass ratio of the iron source to the lithium source is 1:(0.8-1.5); in some embodiments of the present invention, the mass ratio of the iron source to the lithium source is 1:(1-1.2); non-limiting specific examples are 1:1, 1:1.02, 1:1.05, 1:1.08, 1:1.1, 1:1.12, 1:1.15 or 1:1.2.
[0107] In some embodiments of the present invention, the phosphorus source includes at least one of monoammonium hydrogen phosphate, diammonium hydrogen phosphate, ammonium phosphate, lithium phosphate or iron phosphate; in some specific embodiments of the present invention, the phosphorus source includes at least one of monoammonium hydrogen phosphate, diammonium hydrogen phosphate or lithium phosphate; in some examples of the present invention, the phosphorus source is selected from diammonium hydrogen phosphate.
[0108] In some embodiments of the present invention, the mass ratio of the iron source to the phosphorus source is 1:(0.5-2); in some embodiments of the present invention, the mass ratio of the iron source to the phosphorus source is 1:(0.7-1.5); in some embodiments of the present invention, the mass ratio of the iron source to the phosphorus source is 1:(0.8-1.2); non-limiting specific examples are 1:0.8, 1:0.85, 1:0.9, 1:0.95, 1:1, 1:1.05, 1:1.1, 1:1.15 or 1:1.2.
[0109] In some embodiments of the present invention, a drying step is further included before sintering; in some specific embodiments of the present invention, the drying method is selected from spray drying.
[0110] In some embodiments of the present invention, the drying temperature of drying is 80-180°C; in some specific embodiments of the present invention, the drying temperature of drying is 90-160°C; in some examples of the present invention, the drying temperature of drying is 100-150°C; non-limiting specific examples are 100°C, 110°C, 120°C, 130°C, 140°C or 150°C.
[0111] In some embodiments of the present invention, a crushing step is further included after sintering; in some specific embodiments of the present invention, the crushing method is selected from air flow crushing.
[0112] In some embodiments of the present invention, the airflow pressure of airflow crushing is 4 to 10 MPa; in some specific embodiments of the present invention, the airflow pressure of airflow crushing is 5 to 9 MPa; in some examples of the present invention, the airflow pressure of airflow crushing is 6 to 8 MPa; non-limiting specific examples are 6 MPa, 6.5 MPa, 6.8 MPa, 7 MPa, 7.5 MPa, 7.8 MPa or 8 MPa.
[0113] In some embodiments of the present invention, a screening step is further included after crushing; in some specific embodiments of the present invention, the screening method is selected from vibration screening.
[0114] In some embodiments of the present invention, the mesh size of the sieve used for screening is 200-600 mesh; in some specific embodiments of the present invention, the mesh size of the sieve used for screening is 250-550 mesh; in some examples of the present invention, the mesh size of the sieve used for screening is 300-500 mesh; non-limiting specific examples are 300 mesh, 350 mesh, 400 mesh, 450 mesh or 500 mesh.
[0115] A third aspect of the embodiments of the present invention provides a lithium iron phosphate positive electrode material, comprising a positive electrode lithium supplement and the lithium iron phosphate modified material of the first aspect of the embodiments of the present invention.
[0116] The lithium iron phosphate modified material provided in the embodiment of the present invention has a good absorption effect on oxygen by introducing structural defects. Therefore, when combined with a positive electrode lithium replenisher, it can effectively absorb the oxygen generated by the positive electrode lithium replenisher, thereby solving the gas production problem caused by the introduction of the positive electrode lithium replenisher, thereby obtaining a high-energy, high-power lithium iron phosphate positive electrode material.
[0117] In some embodiments of the present invention, the positive electrode lithium replenisher includes lithium-rich iron oxide (Li5FeO4, LFO), lithium nickel oxide (Li2NiO2, LNO) or a combination thereof; in some specific embodiments of the present invention, the positive electrode lithium replenisher is selected from lithium-rich iron oxide (Li5FeO4, LFO).
[0118] In some embodiments of the present invention, the content of the positive electrode lithium replenisher in the lithium iron phosphate positive electrode material is 0.3-2wt%; in some specific embodiments of the present invention, the content of the positive electrode lithium replenisher in the lithium iron phosphate positive electrode material is 0.4-1.5wt%; in some examples of the present invention, the content of the positive electrode lithium replenisher in the lithium iron phosphate positive electrode material is 0.5-1.2wt%; non-limiting specific examples are 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1wt%, 1.1wt% or 1.2wt%.
[0119] In some embodiments of the present invention, the mass ratio of the lithium iron phosphate modified material to the positive electrode lithium replenisher is 100:(0.5~2); in some specific embodiments of the present invention, the mass ratio of the lithium iron phosphate modified material to the positive electrode lithium replenisher is 100:(0.7~1.5); in some examples of the present invention, the mass ratio of the lithium iron phosphate modified material to the positive electrode lithium replenisher is 100:(0.8~1); non-limiting specific examples are 100:0.8, 100:0.82, 100:0.85, 100:0.88, 100:0.9, 100:0.95 or 100:1.
[0120] In some embodiments of the present invention, the lithium iron phosphate positive electrode material further includes a positive electrode conductor, a positive electrode binder or a combination thereof; in some specific embodiments of the present invention, the lithium iron phosphate positive electrode material further includes a positive electrode conductor and a positive electrode binder.
[0121] In some embodiments of the present invention, the positive electrode conductive agent includes at least one of conductive carbon black, carbon nanotubes, acetylene black or graphene; in some specific embodiments of the present invention, the positive electrode conductive agent includes conductive carbon black (SP) and carbon nanotubes (CNT); the mass ratio of conductive carbon black (SP) and carbon nanotubes (CNT) can be 1: (0.5~2), specifically 1:0.5, 1:0.8, 1:1, 1:1.2, 1:1.5 or 1:2.
[0122] In some embodiments of the present invention, the mass ratio of the lithium iron phosphate modified material to the positive electrode conductive agent is 100:(0.8~2.5); in some specific embodiments of the present invention, the mass ratio of the lithium iron phosphate modified material to the positive electrode conductive agent is 100:(1~2); in some examples of the present invention, the mass ratio of the lithium iron phosphate modified material to the positive electrode conductive agent is 100:(1.2~1.8); non-limiting specific examples are 100:1.2, 100:1.3, 100:1.4, 100:1.5, 100:1.6, 100:1.7 or 100:1.8.
[0123] In some embodiments of the present invention, the positive electrode binder includes an oily binder, an aqueous binder or a combination thereof; an oily binder such as polyvinylidene fluoride (PVDF), and an aqueous binder such as carboxymethyl cellulose, polyacrylic acid, polymethyl methacrylate, etc.; in some specific embodiments of the present invention, the positive electrode binder is selected from an oily binder; in some specific embodiments of the present invention, the positive electrode binder is selected from polyvinylidene fluoride (PVDF).
[0124] In some embodiments of the present invention, the mass ratio of the lithium iron phosphate modified material to the positive electrode binder is 100:(1~3); in some specific embodiments of the present invention, the mass ratio of the lithium iron phosphate modified material to the positive electrode binder is 100:(1.2~2.5); in some examples of the present invention, the mass ratio of the lithium iron phosphate modified material to the positive electrode binder is 100:(1.5~2.2); non-limiting specific examples are 100:1.5, 100:1.6, 100:1.7, 100:1.8, 100:1.9, 100:2, 100:2.1 or 100:2.2.
[0125] In some embodiments of the present invention, the mass ratio of lithium iron phosphate modified material, positive electrode lithium replenisher, positive electrode conductive agent and positive electrode binder is 100: (0.5-2): (0.8-2.5): (1-3); In some specific embodiments of the present invention, the mass ratio of lithium iron phosphate modified material, positive electrode lithium replenisher, positive electrode conductive agent and positive electrode binder is 100: (0.7-1.5): (1-2): (1.2-2.5); In some examples of the present invention, the mass ratio of lithium iron phosphate modified material, positive electrode lithium replenisher, positive electrode conductive agent and positive electrode binder is 100: (0.7-1.5): (1-2): (1.2-2.5). The mass ratio of the positive electrode conductive agent to the positive electrode binder is 100: (0.8-1): (1.2-1.8): (1.5-2.2); non-limiting specific examples include 100: 0.8: 1.2: 1.5, 100: 0.82: 1.4: 1.8, 100: 0.85: 1.4: 1.7, 100: 0.88: 1.5: 1.8, 100: 0.9: 1.6: 1.9, 100: 0.95: 1.7: 2 or 100: 1: 1.8: 2.2.
[0126] A fourth aspect of the embodiments of the present invention provides a battery, comprising the lithium iron phosphate positive electrode material of the third aspect of the embodiments of the present invention.
[0127] The lithium iron phosphate positive electrode material provided in the embodiment of the present invention has low gas production and has the characteristics of high energy and high power. A battery with excellent electrochemical performance can be obtained by using it as a positive electrode material.
[0128] In some embodiments of the present invention, the battery is a lithium-ion battery.
[0129] In some embodiments of the present invention, the battery further comprises a negative electrode material, an electrolyte and a separator.
[0130] In some embodiments of the present invention, the negative electrode material includes a negative electrode active material, a negative electrode conductor and a negative electrode binder.
[0131] In some embodiments of the present invention, the negative electrode active material includes at least one of graphite, silicon-based materials or tin alloys; in some specific embodiments of the present invention, the negative electrode active material is selected from graphite.
[0132] In some embodiments of the present invention, the negative electrode conductive agent includes at least one of conductive carbon black, carbon nanotubes, acetylene black or graphene; in some specific embodiments of the present invention, the negative electrode conductive agent includes conductive carbon black (SP).
[0133] In some embodiments of the present invention, the negative electrode binder includes at least one of polyvinylidene fluoride, carboxymethyl cellulose, styrene butadiene rubber or polyvinyl alcohol; in some specific embodiments of the present invention, the negative electrode binder includes carboxymethyl cellulose (CMC) and styrene butadiene rubber (SBR); the mass ratio of carboxymethyl cellulose (CMC) and styrene butadiene rubber (SBR) can be 1: (0.5-2), specifically 1:0.5, 1:0.8, 1:1, 1:1.2, 1:1.5, 1:1.8 or 1:2.
[0134] In some embodiments of the present invention, the mass ratio of the negative electrode active material, the negative electrode conductive agent and the negative electrode binder is 100: (0.3-2): (1-3); in some specific embodiments of the present invention, the mass ratio of the negative electrode active material, the negative electrode conductive agent and the negative electrode binder is 100: (0.4-1.8): (1.2-2.8); in some examples of the present invention, the mass ratio of the negative electrode active material, the negative electrode conductive agent and the negative electrode binder is 100: (0.5-1.5): (1.5-2.5); non-limiting specific examples are 100: 0.5: 1.5, 100: 0.8: 1.8, 100: 1: 2, 100: 1.2: 2.2 or 100: 1.5: 2.5.
[0135] The present invention is further described below in conjunction with more specific embodiments, application examples and comparative examples.
[0136] Example 1
[0137] A lithium iron phosphate modified material, the structural schematic diagram of which is as follows Figure 1 As shown, it specifically includes: lithium iron phosphate particles 1, a coating layer 3 coated on the surface of the lithium iron phosphate particles 1, and a carbon layer 2 coated on the surface of the coating layer 3.
[0138] The preparation flow chart of the lithium iron phosphate modified material is as follows: Figure 2 As shown, the specific steps are as follows:
[0139] 1) Weigh a certain proportion of iron source (FeC2O4·2H2O), lithium source (Li2CO3), phosphorus source (NH4H2PO4), carbon source (glucose), and additives (TiO2 and Co3O4), wherein the mass ratio of iron source, lithium source, phosphorus source, carbon source, and additive is 1:1.02-1.05:1:0.012:0.01, and set aside;
[0140] 2) Pretreatment (oxygen defect built-in): the additive is ball-milled in a ball mill at a speed of 1000 r / min for 2 hours, and then the ball-milled additive is first mixed with the carbon source, and the ball mill is used for 24 to 48 hours to mix evenly, and then placed in an ultrasonic wave for 1 hour, and the ultrasonic power is set between 20 and 40 kHz to obtain a pretreated mixture;
[0141] 3) Mixing: Mix the pretreated mixture with the iron source, lithium source and phosphorus source in ethanol solution to react and obtain lithium iron phosphate; the reaction equation of the process is: 2FeC2O4·2H2O+Li2CO3+2NH4H2PO4→2LiFePO4+2CO2↑+2CO↑+C+7H2O+2NH3↑;
[0142] 4) Drying: spray drying the wet mixed lithium iron phosphate at 100-150° C. to obtain a dry material;
[0143] 5) Pre-sintering and sintering: The above dry materials are placed in a sintering device at an ultra-high heating rate (10000℃ / min), and a protective atmosphere (N2, Ar) is introduced into the furnace. The purity of the atmosphere needs to reach 99.9%, and the airtightness during the sintering process must be ensured. The oxygen content in the furnace is kept below 50ppm. The temperature is raised to 780℃ within 2s, kept at this temperature for 23s, and then annealed for 2s;
[0144] 6) Crushing and screening: After sintering is completed, further air flow crushing is required, and the air flow pressure is 6-8MPa to achieve the particle fineness required by the process. The final particle size distribution requires concentrated particles, normal distribution, and as few fine powders and large particles as possible. Finally, the material is screened through a 400-mesh vibrating screen to remove large particles and impurities to obtain qualified lithium iron phosphate.
[0145] The technical indicators of the lithium iron phosphate modified material obtained in this example are as follows (the carbon content is tested by a carbon sulfur instrument, and the metal content is tested by ICP):
[0146] Li content: 4.40±0.5wt%; Fe content: 33.4±1.0wt%; P content: 19.2±1wt%; C content: 1.15±0.2wt%; D10: 0.5±0.1μm; D50: 1.3±0.5μm; D90: 4.0±1.5μm; D99: <10μm; (D90-D10) / D50: 2.8±1.0 (unit is 1); compacted density: >2.50g / cm 3 ; Tap density: 1.0±0.3g / cm 3 ; Powder resistivity: ≤25Ω·cm; Specific surface area: 13.0±1.5m 2 / g; Water content: <800ppm; pH: 9.5±0.5; Residual lithium: ≤400ppm; Impurity content: Na+K≤350ppm; Ca+Mg≤300ppm; Cu+Zn≤50ppm; S≤200ppm; Mn≤200ppm; Magnetic substance: ≤500ppb; Number of magnetic metal particles: ≤95pcs / kg; First discharge specific capacity: ≥156mAh / g; First coulombic efficiency: ≥96%.
[0147] Figure 3 This is a SEM image of a part of the lithium iron phosphate modified material of Example 1. Figure 4 This is a SEM image of another part of the lithium iron phosphate modified material of Example 1. Figures 3-4 It can be seen that the surface of the product particles has a floc-like coating layer. Combined with the characterization of carbon content and metal content, it can be determined that what is obtained in Example 1 is a lithium iron phosphate modified material with a specific coating structure.
[0148] Example 2
[0149] A lithium iron phosphate modified material, which is different from Example 1 in that, in this example, the mass ratio of the iron source, lithium source, phosphorus source, carbon source, and additive is 1:1.02-1.05:1:0.012:0.02, and the specific raw materials and preparation method are the same as those in Example 1.
[0150] Example 3
[0151] A lithium iron phosphate modified material, which is different from Example 1 in that, in this example, the mass ratio of the iron source, lithium source, phosphorus source, carbon source, and additive is 1:1.02-1.05:1:0.012:0.005, and the specific raw materials and preparation method are the same as those in Example 1.
[0152] Example 4
[0153] A lithium iron phosphate modified material, which is different from Example 1 in that the additive in this example is only TiO2, and other raw materials, amounts and preparation methods are the same as those in Example 1.
[0154] Comparative Example 1
[0155] A lithium iron phosphate modified material, which differs from Example 1 in that no additive is added in this example, and other raw materials, amounts and preparation methods are the same as those in Example 1.
[0156] The structural diagram of Comparative Example 1 is as follows Figure 5 As shown, it includes lithium iron phosphate particles 1 and a carbon layer 2 coated on the surface of the lithium iron phosphate particles 1. Compared with the structural schematic diagram of Example 1, it can be seen that the comparative example 1 does not form a coating layer 3 because no transition metal oxide is added.
[0157] Comparative Example 2
[0158] A lithium iron phosphate modified material, which differs from Example 1 in that, in step 5) of the preparation process of this example, a conventional tubular furnace is used as the sintering equipment, the heating rate is 5°C / min, after heating to 780°C, it is kept warm for 10 hours, and conventional cooling annealing is performed, and the other preparation steps and specific raw materials and amounts are the same as those in Example 1.
[0159] Comparative Example 3
[0160] A lithium iron phosphate modified material, which differs from Example 1 in that the preparation process of this example does not include step 2), that is, the additive is not pretreated, and the additive is not mixed with the carbon source in advance; in step 3), the additive, carbon source, iron source, lithium source, and phosphorus source are mixed together in an ethanol solution, and the other preparation steps and specific raw materials and amounts are the same as those in Example 1.
[0161] Application Examples 1 to 4 and Application Comparative Examples 1 to 3
[0162] Application Examples 1 to 4 and Application Comparative Examples 1 to 3 each provide a lithium ion battery, which is prepared by the following steps:
[0163] 1) Preparation of lithium iron phosphate positive electrode sheet: The lithium iron phosphate modified materials obtained in Examples 1 to 4 and Comparative Examples 1 to 3 are mixed with LFO (positive electrode lithium supplement), SP, CNT, and PVDF, and the mass ratio of lithium iron phosphate modified materials, LFO, SP, CNT, and PVDF is 96:0.8:0.8:0.6:1.8, and then N-methylpyrrolidone is added and dispersed in a negative pressure high-speed disperser to finally obtain a positive electrode slurry with good fluidity. Then the positive electrode slurry is evenly coated on aluminum foil, dried at room temperature, transferred to an oven for further drying, and then cold pressed, slit, and cut to obtain a positive electrode sheet.
[0164] 2) Preparation of negative electrode sheets: negative electrode active materials graphite, SP, CMC, and SBR are mixed in a mass ratio of 96.0:1.0:1.6:1.4, added to deionized water, and stirred to a uniform system to obtain negative electrode slurry; the negative electrode slurry is evenly coated on a copper foil, dried at room temperature, and then transferred to an oven for further drying, and then cold pressed, slit, and cut to obtain negative electrode sheets.
[0165] 3) Battery assembly: stacking the lithium iron phosphate positive electrode sheet, the isolation membrane, and the negative electrode sheet in order to finally obtain a bare battery cell; placing the bare battery cell in an outer packaging shell, injecting an electrolyte after drying, vacuum packaging, standing, forming, exhausting, and volume separation, finally obtaining the lithium-ion batteries of application examples 1 to 4 and application comparison examples 1 to 3, respectively.
[0166] Performance Testing
[0167] (1) The lithium ion batteries of Application Examples 1 to 4 and Application Comparative Examples 1 to 3 were tested for DC internal resistance DCIR during discharge at different states of charge (SOC%) at -20°C. The results are shown in Table 1.
[0168] Table 1 Discharge DCIR (unit: mΩ) of lithium ion batteries of application examples 1 to 4 and application comparative examples 1 to 3 at -20°C
[0169] project 90% SOC 80% SOC 50% SOC 20% SOC 10% SOC Application Example 1 190.57 214.67 230.46 262.06 275.81 Application Example 2 195.62 215.78 240.32 275.07 278.54 Application Example 3 198.34 218.65 246.54 280.43 290.34 Application Example 4 200.89 225.63 250.83 282.41 298.21 Application Comparative Example 1 211.97 235.40 251.24 288.39 303.92 Application Comparative Example 2 222.13 244.97 263.65 304.36 318.77 Application Comparative Example 3 203.2 231.0 249.1 283.1 302.5
[0170] (2) The lithium ion batteries of Application Examples 1 to 4 and Application Comparative Examples 1 to 3 were tested for DC internal resistance DCIR at -20°C under different states of charge (SOC%). The results are shown in Table 2.
[0171] Table 2 Charging DCIR (unit: mΩ) of lithium ion batteries of application examples 1 to 4 and application comparative examples 1 to 3 at -20°C
[0172] project 90% SOC 80% SOC 50% SOC 20% SOC 10% SOC Application Example 1 213.77 233.85 225.63 226.43 228.42 Application Example 2 215.73 240.29 231.41 233.09 236.01 Application Example 3 216.23 242.20 233.71 235.29 238.91 Application Example 4 225.71 250.29 245.42 246.29 249.02 Application Comparative Example 1 256.07 279.14 260.29 259.54 262.71 Application Comparative Example 2 246.56 271.25 254.48 253.57 257.65 Application Comparative Example 3 234.4 265.3 252.6 249.1 254.3
[0173] (3) 60℃ high temperature storage and normal / high temperature 1C / 1C cycle performance test: First, the battery cell was tested at 0.33C standard capacity at 25℃, and the DCR test was performed before storage. Then, the battery cell was stored at 60℃±2℃, and the battery cell volume, capacity retention rate, recovery rate test, and DCR test were performed every 28 days. The battery cell was stored until 84 days, and the test was performed with a clamp. The battery cell was tested at 0.33C standard capacity at 25℃, and then the 1C / 1C charge and discharge test was performed at 25℃ and 45℃ respectively. The results are shown in Table 3.
[0174] Table 3 High temperature resistance and cycle performance of lithium ion batteries of application examples 1 to 4 and application comparative examples 1 to 3
[0175] As can be seen from Tables 1 to 3, the lithium-ion battery obtained by using the lithium iron phosphate modified material of the embodiment of the present invention has a low internal resistance in both the charging state and the discharging state, can support a high charging rate and a high discharging rate, and has a good rate performance. After the lithium-ion battery in the application embodiment is stored at a high temperature of 60°C for 3 months (84 days), the storage capacity retention rate is ≥88%, the storage capacity recovery rate is ≥90%, and the high temperature resistance and cycle performance are excellent. In the application embodiment of the present invention, only 0.8wt% of the lithium supplement is added, and the charge and discharge capacity is increased by about 1mAh / g compared with the conventional lithium iron phosphate material.
[0176] Comparative Example 1 does not add transition metal oxide, does not form a coating layer including a transition metal doping layer, and cannot introduce structural defects such as oxygen defects in the transition metal doping layer, so the oxygen absorption performance is also poor, and the battery expansion phenomenon is more serious when combined with a lithium supplement. As can be seen from Tables 1 to 3, the lithium ion battery obtained using the material of Comparative Example 1 has a larger internal resistance, a larger cell volume expansion rate, and is not as good as Example 1 in high temperature resistance and cycle performance.
[0177] Comparative Example 2 uses a lower sintering heating rate, which makes it difficult to construct Li-Fe antisite defects and lattice strain in the lithium iron phosphate particles. Therefore, the rate performance, high temperature resistance and cycle performance are poor, and it is also easy to cause battery expansion when combined with a lithium supplement.
[0178] In Comparative Example 3, the carbon source and the transition metal oxide were not pretreated, and the coating uniformity of the carbon layer and the coating layer was poor. Also, since no built-in oxygen defects were formed, the improvement in rate performance and the effect on oxygen absorption were limited. The battery internal resistance, battery cell volume expansion rate, high temperature resistance and cycle performance were not as good as those in Example 1.
[0179] It can be seen that in the embodiment of the present invention, various means such as constructing Li-Fe antisite defects and lattice strain, metal ion doping, oxide inert atmosphere sintering, additive particle size control, etc. are used to realize the construction of oxygen defects in lithium iron phosphate positive electrode materials, which are used to absorb the oxygen released by the lithium supplement agent (such as LFO) during the charge and discharge process due to the balance of redox valence, reduce a series of interface side reactions and gas production caused by oxygen release, thereby realizing a method for preparing a lithium iron phosphate material with high energy, high power and good electrical properties. It can be seen that by regulating the sintering equipment and sintering curve, the amount and type of additives, the performance of charge and discharge DCR, gas production, storage capacity retention and recovery rate, high temperature cycle, etc. can be reduced. Finally, the problem that the prior art does not start from the modification of the lithium iron phosphate material itself to improve the effect of the lithium supplement agent (such as LFO) on the positive electrode material on the storage performance, resulting in only limited optimization results, is solved.
[0180] In the embodiment of the present invention, by optimizing the sintering curve, Li-Fe antisite defects and lattice strain are constructed to improve Li + Transmission efficiency, improve the power characteristics of lithium iron phosphate (LFP); introduce trace metal oxides during the sintering process of lithium iron phosphate to reduce the valence change of Fe ions in LFO, thereby reducing the release of oxygen; secondly, the introduction of unequal metals can form oxygen defects in the structure, which plays a role in absorbing oxygen. The embodiments of the present invention do not need to introduce inactive substances into the system, so the material capacity will not be reduced. Inactive substances such as: oxygen absorbers with low capacity, catalysts that do not provide capacity at all, conductive agents, etc.; the content of transition metal oxides required to be added in the embodiments of the present invention is small, and the metal elements are abundant in resources, the cost is low, and compared with other improvement methods, the present invention has obvious advantages in terms of cost.
[0181] In summary, the present invention is based on the improvement of the lithium iron phosphate material itself, and introduces a transition metal doping layer, in which the doped transition metal elements will generate holes or electrons in the material, and then form structural defects such as oxygen defects, which is beneficial to promote the material's absorption of oxygen and reduce the adverse effects of oxygen released by the lithium supplement.
Claims
1. A lithium iron phosphate modified material, characterized in that: include: Lithium iron phosphate particles, a coating layer coated on at least part of the surface of the lithium iron phosphate particles, and a carbon layer coated on at least part of the surface of the coating layer; the coating layer includes a transition metal doping layer, and the transition metal doping layer contains structural defects.
2. The lithium iron phosphate modified material according to claim 1, characterized in that: The structural defects in the transition metal doped layer include oxygen defects; And / or, the coating layer further comprises a transition metal oxide layer, and the transition metal oxide layer coats at least a portion of the surface of the transition metal doping layer; And / or, the lithium iron phosphate particles contain structural defects; the structural defects in the lithium iron phosphate particles include at least one of Li-Fe antisite defects, dislocations or oxygen defects.
3. The lithium iron phosphate modified material according to claim 1, characterized in that: The transition metal element doped in the transition metal doping layer includes at least one of Ti, Ni, Y, Fe, Ce, W or Co; And / or, the content of transition metal elements in the coating layer is 0.1-1 wt%.
4. A method for preparing a lithium iron phosphate modified material, characterized in that: The following steps are involved: The transition metal oxide is mixed with a carbon source and then pretreated, and then an iron source, a lithium source and a phosphorus source are added and mixed, and then sintered to obtain the lithium iron phosphate modified material as claimed in any one of claims 1 to 3.
5. The preparation method according to claim 4, characterized in that: The heating rate of the sintering is 8000-12000°C / min; And / or, the sintering heating time is 1 to 5 seconds; And / or, the sintering temperature reduction rate is 8000-12000°C / min; And / or, the sintering temperature reduction time is 1 to 5 seconds; And / or, the sintering temperature is 700-900°C; And / or, the sintering holding time is 10 to 100 seconds; And / or, the sintering is performed in a protective gas atmosphere.
6. The preparation method according to claim 4, characterized in that: The pretreatment method includes ball milling, ultrasonic treatment or a combination thereof; the ball milling time is 12 to 60 hours; and / or the ultrasonic treatment time is 0.1 to 5 hours; And / or, the ultrasonic frequency of the ultrasonic treatment is 10 to 50 kHz.
7. The preparation method according to claim 4, characterized in that: Before the transition metal oxide is mixed with the carbon source for pretreatment, the method further includes a step of ball milling the transition metal oxide; the ball milling speed for the transition metal oxide is 500 to 1500 r / min; and / or the ball milling time for the transition metal oxide is 0.5 to 5 hours.
8. The preparation method according to claim 4, characterized in that: The transition metal oxide includes at least one of TiO2, NiO, Y2O3, Fe2O3, CeO2, WO3 or Co3O4; And / or, the mass ratio of the iron source to the transition metal oxide is 1:(0.001-0.1).
9. A lithium iron phosphate positive electrode material, characterized in that: It comprises a positive electrode lithium supplement agent, and the lithium iron phosphate modified material according to any one of claims 1 to 3 or the lithium iron phosphate modified material prepared by the preparation method according to any one of claims 4 to 8; The positive electrode lithium replenisher includes lithium-rich lithium iron oxide, lithium nickel oxide or a combination thereof; and / or the content of the positive electrode lithium replenisher in the lithium iron phosphate positive electrode material is 0.3-2 wt %.
10. A battery, characterized in that: Including the lithium iron phosphate positive electrode material as described in claim 9.
Citation Information
Cited By
Manufacturing process of lithium iron phosphate energy storage battery
CN121123420A